EPIDEMIC OF OBESITY: PREVENTION MUST START IN CHILDHOOD - Khuwaja, Ali Khan (Journal of Ayub Medical College Abbottabad, 2004)
I read with interest the recent article by Qidwai and Azam[1] discussing the issue of obesity. The authors are to be congratulated for preparing such a comprehensive, well-referenced and timely publication. Firstly, it describes the burden of obesity and its associated health hazards. Secondly, it nicely presents that in-spite of better understanding about obesity among study subjects, measures to control body weight are lacking. Authors very rightly stated that study population was not representative of general population of Pakistan. Nevertheless, documented work can provide some insight about this problem, thus, helps to device interventions for prevention and control of obesity. Childhood obesity has reached epidemic proportion; worldwide, approximately 22 million children under five years of age are overweight.2 Large number of epidemiological studies proved obesity as a significant risk factor for cardiovascular diseases. Pathogenesis of atherosclerosis, the underlying cause of cardiovascular disease, begins in early childhood, although it clinically manifests in adulthood.3 It is also evident that risk factors for cardiovascular diseases can best be modified at young ages, as in childhood, thus improve the health outcomes in adult life. Pakistan, where over 43% of the population is comprised of children,4 it was observed that children are adopting more and more unhealthy lifestyles. A trend away from active leisure pursuits and recreational sports has been evident, and reliance on sedentary entertainment, including television, computer and video games has increased. There is also an increasing trend of eating junk and empty caloric foods by children. Khuwaja et al5, found that majority (58%) of the school children had at least one modifiable risk factor for cardiovascular diseases like physical inactivity, unhealthy dietary habits, overweight and obesity. In context of direct and indirect cost, the impact of obesity on the lives of people is devastating when measured in terms of premature morbidity, mortality and disabilities. Pakistan which already has poor health and economic indicators cannot afford the emerging costly epidemic of obesity. Thus, every effort should be made to prevent and modify unhealthy lifestyle by increasing health promotion and disease prevention measures while the condition still is in the early phase. In this regard, it is important for Family Physicians to play a leading role, as they understand the natural history and disease process and are engaged to provide comprehensive preventive and curative health care to all family members including children and adolescents. To promote healthy lifestyle among individuals and families, family physicians should intervene earlier in life thus beating the epidemic of obesity and other lifestyle risk factors for cardiovascular diseases in later life. At the same time, it is important to educate and encourage parents (being a role model) to personally adopt and practice a healthy lifestyle, especially with regard to diet and regular physical activity. There is also an immense need for more research to explore this issue in more details and to find and implement more cost-effective intervention programs in accordance to our culture and needs.